COGNITIVE DEVELOPMENT FEATURES OF STUDENTS IN A DIGITAL LEARNING ENVIRONMENT. (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical possibilities of teaching the subject ofinclusive education in the context of a digital educational environment from both theoretical andpractical perspectives. It substantiates that the processes of digital transformation in the educationsystem create the need for new didactic approaches, interactive methods, and the formation ofindividual learning trajectories. The effectiveness of using digital platforms, distance learningtechnologies, multimedia tools, and adaptive learning systems in teaching inclusive education isalso discussed.
Keywords: inclusive education; adaptive learning; differential approach